Klasterisasi Pengunjung Mall untuk Menentukan Target Pasar Ponsel Terbaru Menggunakan Algoritma K-Means Clustering - Irvansah Satria Pamungkas; Dhimas Maulana Hadi; Gilang Aditya; Rosyidah Astari Nur; Aries Saifudin; Teti Desyani (Jurnal Informatika Universitas Pamulang, 2021)
Every day there are always people who visit the mall with different needs, there are some people who visit the mall to buy cell phones that have the latest features to make them look more updated, some just look around and some are not recommend to buy a new one because he still thinks his phone can still be used. To overcome this, electronic goods sales shops, especially those selling cellphones, need an analysis when they want to sell the latest products. They can group those people with expenditure information and their stages using the Kmeans Clustering algorithm. The results of these people will be divided into several clusters, namely people who will buy, people who might buy or people who will not buy, so when these cellphone distributors want to sell the latest cellphones, they will know how many people have the opportunity to buy the cellphone.